β-Sitosterol From Bark Of Artocarpus Camansi And Its Antidiabetic Activity - Rosnani Nasution; . Marianne; Muhammad Bahi; Nurdin Saidi; Isni Junina (Syiah Kuala University, 2015)
Research compound betasitosterol from the bark of plant of Artocarpus camansi (kulu) and test its antidiabetic has been done. The study begins by extracting samples (3.5 kg),w in the solvent of hexane, hexane extracts obtained,then separated by gravity column chromatography, and was characterized by GC-MS. The results obtained are groups of fractions A, and B. From phytochemical test results, the fraction of group B, has a steroid framework. Group fractions B after rechromatographed is obtained a pure isolates of B. Characterization by 1H-NMR and MS (from GC-MS), pure isolate of B is β-sitosterol. Antidiabetic activity test results showed that the extract of n-hexane, fraction group A and fraction group of B (containing βsitosterol), can lower blood sugar levels male Swiss Webster mice were performed by the method of glucose tolerance. Dose of extract of n-hexane is 50 mg/dL at minute 30th, 60th and 90th can lower glucose as much as 103 mg/dL; 71 mg/dL; and 49.33 mg/dL. Group of fraction A of a dose 50 mg/dL at 60th minutes and 90th can lower blood glucose of mice are: 116 mg/dL; and 58 mg/dL. Group B fraction (containing β-sitosterol) at a dose of 50 mg/dL at minute 30th, 60th and 90th can lower glucose by 73 mg/dL; 87 mg/dL; and 73.33 mg/dL. Group fraction of B is the highest in lowering blood glucose average compared with n-hexane extract and group A. Analysis of variance of this fraction were performed by using ANOVA Post hoc analysis procedures one-way of, significant differences (p0.05) and (p 0.01) conducted using Tukey.